Unusual Postrhinoplasty Complication: Nasal Dorsum Cyst - Pier Giorgio Giacomini; Davide Topazio; Roberta Di Mauro; Stelio Mocella; Matteo Chimenti; Stefano Di Girolamo (Case Reports in Otolaryngology)
Among all the possible complications of aesthetic rhinoplasty, a rare one is the development of cystic masses on the nasal dorsum: several theories suggest that cysts develop commonly by entrapment of nasal mucosa in the subcutaneous space, but they can also originate from foreign body reactions. This report deals with two cases of nasal dorsum cysts with different pathogenesis: both patients had undergone aesthetic rhinoplasty in the past (26 years ago and 14 years ago, resp.). Both cystic masses were removed via a direct open approach and nasal reconstruction was performed successfully with autologous vomer bone. The pathologic investigations showed a foreign body inclusion cyst associated with latex rubber in the first case and a sequestration of a mucosal-lined nasal bone was not removed at the time of primary rhinoplasty in the second case. A brief review of the literature focuses on the pathophysiology and treatment options for nasal dorsal cysts following aesthetic rhinoplasty.